Active Share and the Three Pillars of Active Management: Skill, Conviction, and Opportunity. Issue 2 (1st April 2017) - Cremers, Martijn
Abstract : This article relates Active Share to the fund manager's individual stock-picking skill, conviction, and opportunity. I propose a new formula for Active Share that emphasizes that a fund's Active Share is reduced only through overlapping holdings with its benchmark. I show why and how to adjust the expense ratio for the level of Active Share and the cost of investing in the benchmark. I conclude that Active Share matters for the performance of actively managed funds. Investors should not pay (too) much for low–Active Share funds, which generally underperform. But there is no evidence that high–Active Share funds as a group have underperformed, and patient managers with high Active Share have been quite successful. Abstract : A practitioner's perspective on this article is provided in the In Practice piece "Why Should We Care about Active Share? " by Phil Davis, online 20 March 2017. Disclosure: The data on Active Share and fund holding duration used in this study are available at http://activeshare.nd.edu for academic purposes. Active Share and Active Fee information (as well as other related holdings-based information) for US equity funds is available at http://activeshare.info . I consult with investment firms that offer high–Active Share investments. Editor's Notes: This article was externally reviewed using our double-blind peer-review process. When the article was accepted for publication, the authors thanked the reviewers in their acknowledgments. David Blitz was one of the reviewers for this article. Submitted 10 August 2016 Accepted 28 December 2016 by Stephen J. Brown